Intra-Quranic connections in Sunni and Shiâi tafsirs: a meeting point or another area of contestation? - Rohman, Izza (Indonesian Journal of Islam and Muslim Societies, 2013)
This study seeks to shed light on how a celebrated interpretive approach to theQuran considered to be most objective is taken by interpreters from differenttheological settings. It takes a closer look at how the principle of tafsi>r al-Qurâa>nbi al-Qurâa>n (interpretation of the Quran by the Quran) is employed by al-Shanqitiin his Ad}wa>â al-Baya>n and al-Tabatabaâi in his al-Mi>za>n, taking their interpretationof ahl al-bayt as a main case in point. Noticing how their differences in this issuecan be associated with their respective Sunni and Shiâi backgrounds, this studyfinds a number of areas where both modern exegetes â and other exegetes mostlikely â might be influenced by any creeping theological preference in their pur-suit of objectivity and openness to the text.Kajian ini bermaksud menelaah bagaimana sebuah pendekatan penafsiran al-Qurâan yang dianggap paling objektif diterapkan oleh para mufasir dari latarbelakang aliran teologi yang berbeda. Bagaimana prinsip menafsirkan al-Qurâandengan al-Qurâan diaplikasikan oleh al-Shanqiti dalam tafsirnya, Ad}wa>â al-Baya>n,dan al-Tabatabaâi dalam tafsirnya, al-Mi>za>n, dilihat lebih saksama terutama denganmengambil contoh penafsiran mereka tentang ahlulbait. Mencermati bagaimana perbedaan mereka dalam menafsirkan cakupan ahlul bait bisa dikaitkan denganlatar belakang Sunni dan Syiah mereka, kajian ini menemukan sejumlah ranah dimana kedua mufasir modern ini â dan sepertinya juga mufasir yang lain â bisasajaÂ  dipengaruhiÂ  olehÂ  kecenderunganÂ  teologisÂ  ketikaÂ  mencobaÂ  menjagaobjektivitas dan keterbukaan terhadap teks al-Qurâan.